Hantaan virus-derived peptides that stabilize HLA-E could abrogate inhibition of CD56dimNKG2A+ NK cells. - Manling Xue; Kang Tang; Yusi Zhang; Xiaoyue Xu; Chunmei Zhang; Jiajia Zuo; Fenglan Wang; Xiyue Zhang; Xuyang Zheng; Ran Zhuang; Yun Zhang; Boquan Jin; et al. (PLoS Pathogens)
NK cells could participate in the pathogenesis process of virus infectious diseases through the inhibitory receptor CD94/NKG2A interacting with HLA-E/virus-derived peptide complex. However, the effects and mechanisms of NKG2A-HLA-E axis-mediated NK cell responses in hemorrhagic fever with renal syndrome (HFRS) caused by Hantaan virus (HTNV) infection remain unclear. Single-cell RNA sequencing and flow cytometry were employed to analyze the phenotype and function of different NK cell subsets in HFRS patients. The K562/HLA-E cells binding assay was used for peptide affinity detection. The binding capacity of HLA-E/peptide-CD94/NKG2A was detected using ligand-receptor binding assay and tetramer staining. The cytotoxicity assay of NK cells against peptide-pulsed K562/HLA-E cells was conducted for functional evaluation. In this study, CD56dimCD16+NKG2A+ NK cells were the main subset in HFRS patients, showing activation and proliferation phenotypes with NKG2C-CD57- and the ability to secrete tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ) and cytotoxic mediators. Notably, none of the four identified HTNV epitopes presented by HLA-E could be recognized by CD94/NKG2A on CD56dimNKG2A+ NK cells. Furthermore, the subset of CD56dimNKG2A+ NK cells showed the enhanced cytolytic capacity against HTNV peptide pulsed K562/HLA-E cells ex vivo. Taken together, the findings demonstrate that HTNV-derived peptides presented by HLA-E could "abrogate" the inhibition of CD56dimNKG2A+ NK cells, contributing to the antiviral immune response in HFRS patients.